Study on Adsorption of Cu and Ba from Aqueous Solutions Using Nanoparticles of Origanum (OR) and Lavandula (LV) - Ghadah M. Al-Senani; Foziah F. Al-Fawzan (Bioinorganic Chemistry and Applications)
Wild herbs (Origanum (OR) and Lavandula (LV)) were used as environment-friendly adsorbents in this study. The adsorbents were used for adsorption of Cu and Ba from water. The adsorption of heavy metals onto OR and LV was dependent on particle size, dose, and solution pH. The diameter of adsorbent particles was less than 282.8 nm. The adsorption follows second-order kinetics. Langmuir and Freundlich models have been applied to describe the equilibrium data, and the thermodynamic parameters, the Gibbs free energy, ∆G°, enthalpy, ∆H°, and entropy, ∆S°, have been determined. The positive value of ∆H° suggests that the adsorption of heavy metals by the wild herbs is endothermic. The negative values of ∆G° at all the studied temperatures indicate that the adsorption is a spontaneous process. It can be concluded that OR and LV are promising adsorbents for the removal of heavy metals from aqueous solutions over a range of concentrations.